Introducing Old Testament theology: creation, covenant, and prophecy in the divine-human relationship - Bellinger, W. H. Jr. (Baker Academic, a division of Baker Publishing Group, 2022)
1. Beginnings -- 2. A shape for Old Testament theology -- 3. Pentateuch -- 4. Historical books -- 5. Psalms -- 6. Wisdom -- 7. Prophecy.